Air pollution over the North China Plain and its implication of regional transport: A new sight from the observed evidences. (March 2018) - Ge, Baozhu; Wang, Zifa; Lin, Weili; Xu, Xiaobin; Li, Jie; Ji, Dongshen; Ma, Zhiqiang
Abstract: High concentrations of the fine particles (PM2.5 ) are frequently observed during all seasons over the North China Plain (NCP) region in recent years. In NCP, the contributions of regional transports to certain area, e.g. Beijing city, are often discussed and estimated by models when considering an effective air pollution controlling strategy. In this study, we selected three sites from southwest to northeast in NCP, in which the concentrations of air pollutants displayed a multi-step decreasing trend in space. An approach based on the measurement results at these sites has been developed to calculate the relative contributions of the minimal local emission (MinLEC) and the maximum regional transport (MaxRTC) to the air pollutants (e.g., SO2, NO2, CO, PM2.5 ) in Beijing. The minimal influence of local emission is estimated by the difference of the air pollutants' concentrations between urban and rural areas under the assumption of a similar influence of regional transport. Therefore, it's convenient to estimate the contributions of local emission from regional transport based on the selective measurement results instead of the complex numerical model simulation. For the whole year of 2013, the averaged contributions of MinLEC (MaxRTC) for NO2, SO2, PM2.5 and CO are 61.7% (30.7%), 46.6% (48%), 52.1% (40.2%) and 35.8% (45.5%), respectively. The diurnal variation of MaxRTC for SO2, PM2.5 and CO shows an increased pattern during the afternoon and reached a peak (more than 50%) around 18:00, which indicates that the regional transport is the important role for the daytime air pollution in Beijing. Graphical abstract: Highlights: The concentrations of air pollutants displayed a multi-step decreasing trend from southwest to northeast in NCP. We developed an approach to estimate the contributions of local emission from regional transport to the air pollutants. Contribution of local emission to NO2 and PM2.5 is more than that of regional transport, while SO2 and CO is on the contrary. Regional transport influences will increase during afternoon and reach the highest at around 18:00. Abstract : In this work, we establish an observation-based method, which is proved to be an effective and convenient way for estimating the local and transport contributions to the air pollution in Beijing.